What Can the Service Delivery Indicator Surveys Tell Us about COVID-19 Preparedness? - Sharma, Jigyasa; Andrews, Kathryn; Conner, Ruben; Gatti, Roberta (World Bank, Washington, DC, 2020)
To aid national and international efforts to support countries in enhancing their pandemic preparedness in the face of COVID-19, this paper draws from the World Bank's Service Delivery Indicator surveys to highlight key aspects of health service preparedness in Kenya, Sierra Leone, and Tanzania. The results of this analysis paint a highly variable picture. At least 10 percent of lower-level facilities in all three countries have inpatient care capacity, suggesting that these lower-level facilities could help absorb surges in patient flow. Less than half of the facilities in the three countries have a fixed or mobile phone and less than a third have internet access, suggesting a likely challenge in communication and timely sharing of essential information. Concerningly, less than half of the facilities have appropriate handwashing facilities for patients, with even lower rates in rural areas. Between 80 and 95 percent of the facilities have a thermometer to diagnose fever, but availability of a thermometer, stethoscope, and blood pressure cuff together is variable (ranging from almost 90 percent of the facilities in Tanzania to less than 65 percent in Sierra Leone). The paper concludes by highlighting key innovations for future surveys to improve measurement of pandemic preparedness.